The implications of adopting the model of complete harmonization (a case study) - Stefanicki, Robert (University of Wroclaw. Faculty of Law, Administration & Economics, 2011)
Significant difficulties in the practical application of the transposed legislation appear in the model of complete harmonization. They cover both the more precisely-defined scope of the Directive on unfair B2C commercial practice, as well as the possibility of maintaining national derogations from the exhaustive list set out in detail concerning absolute prohibitions effective in all conditions. These issues concern the judgment of the Court of Justice in the Mediaprint Zeitungs- und Zeitschriftenverlag GmbH & Co KG case, in which it ‘...hereby rules, that the Directive must be interpreted as precluding a national provision, such as that at issue in the main proceedings, which lays down a general prohibition on sales with bonuses and is not only designed to protect consumers but also pursues other objectives.’ It is desirable that those commercial practices which are in all circumstances unfair be identified to provide greater legal certainty. Lists of unfair clauses make it easier for traders, consumers, and courts or authorities to determine the meaning of the general clause. Member States may not adopt stricter rules than those provided for in the Directive, even in order to achieve a higher level of consumer protection. But the far-reaching consequence discussed in the paper justifies posing questions about the best level of consumer protection and which harmonization regime should be chosen for it.
Keywords: Dyrektywy o nieuczciwych praktykach handlowych B2C; wyrok Trybunału Sprawiedliwości; sprawa Mediaprint Zeitungs- und Zeitschriftenverlag GmbH & Co KG